Stochastic models of progression of cancer and their use in controlling cancer-related mortality - Kimmel, Marek; Gorlova, Olga Y. (Zielona Góra: Uniwersytet Zielonogórski)
A construction of a realistic statistical model of lung cancer risk and progression is proposed. The essential elements of the model are genetic and behavioral determinants of susceptibility, progression of the disease from precursor lesions through early (localized) tumors to disseminated disease, detection by various modalities, and medical intervention.
Keywords: lung cancer; genetic susceptibility; environmental exposure; tumor growth; statistical modeling; simulation